2011
DOI: 10.1002/hbm.21363
|View full text |Cite
|
Sign up to set email alerts
|

Functional MRI assessment of orofacial articulators: Neural correlates of lip, jaw, larynx, and tongue movements

Abstract: Compared with complex coordinated orofacial actions, few neuroimaging studies have attempted to determine the shared and distinct neural substrates of supralaryngeal and laryngeal articulatory movements when performed independently. To determine cortical and subcortical regions associated with supralaryngeal motor control, participants produced lip, tongue and jaw movements while undergoing functional magnetic resonance imaging (fMRI). For laryngeal motor activity, participants produced the steady-state/i/vowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
131
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(160 citation statements)
references
References 87 publications
(170 reference statements)
26
131
3
Order By: Relevance
“…Neural populations in proximity to the peaks of these clusters have been attributed to the sensorimotor control of movements of the lips, tongue, jaw, and larynx (e.g., Grabski et al, 2012;Bohland & Guenther, 2006;Pulvermüller et al, 2006) and have been shown to produce speech through highly coordinated sequences of spatial patterns of activity that hierarchically represent the articulatory features of phonemes (Bouchard, Mesgarani, Johnson, & Chang, 2013). Furthermore, activity in these speech production areas, especially in the left hemisphere, has also been demonstrated for the passive perception of speech sounds (Pulvermüller et al, 2006;Wilson, Saygin, Sereno, & Iacoboni, 2004), supporting theories postulating a motor involvement in speech perception (Galantucci, Fowler, & Turvey, 2006;Liberman, Cooper, Shankweiler, & Studdert-Kennedy, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…Neural populations in proximity to the peaks of these clusters have been attributed to the sensorimotor control of movements of the lips, tongue, jaw, and larynx (e.g., Grabski et al, 2012;Bohland & Guenther, 2006;Pulvermüller et al, 2006) and have been shown to produce speech through highly coordinated sequences of spatial patterns of activity that hierarchically represent the articulatory features of phonemes (Bouchard, Mesgarani, Johnson, & Chang, 2013). Furthermore, activity in these speech production areas, especially in the left hemisphere, has also been demonstrated for the passive perception of speech sounds (Pulvermüller et al, 2006;Wilson, Saygin, Sereno, & Iacoboni, 2004), supporting theories postulating a motor involvement in speech perception (Galantucci, Fowler, & Turvey, 2006;Liberman, Cooper, Shankweiler, & Studdert-Kennedy, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that the ISC found in these regions could be related to some form of motor simulation (Rizzolatti and Sinigaglia, 2010). However, the particular region in the postcentral gyrus (BA40) where ISC was found has also been reported during facial movements, including facial expressions (Grabski et al, 2012;Lee et al, 2006;Lowell et al, 2008). Thus, another possible explanation for finding BA40 in the difference map is that the Edited condition The finding of greater ISC in the primary auditory cortex for the Unedited condition is consistent with the findings of Hasson and colleagues (Hasson et al, 2010), who found that when viewing an edited video, there was a slight negative inter-region correlation between the primary auditory cortex and the primary visual cortex.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…. ], the supplementary motor area and the superior cerebellar hemispheres" (Grabski et al, 2012b) on both hemispheres as well as orofacial motor control in the central sulcus, rostral region of the precentral gyrus, and the caudal areas in the postcentral gyrus bilaterally (Grabski et al, 2012a). Singing and speaking show bilateral activation in the inferior pre-and postcentral gyrus, the superior temporal gyrus, and the superior temporal sulcus (Özdemir et al, 2006).…”
Section: Production Performance In Singing and Speakingmentioning
confidence: 99%